The formative period in Alabama, 1815-1828 - Abernethy, Thomas Perkins, 1890-1975 (Library of Alabama classics., 1990)
Traces the evolution of Alabama out of the Mississippi Territory, and the earliest years of statehood. Events in these early years established patterns and shaped the future.